Ferritin heavy/light chain (FTH1/FTL) expression, serum ferritin levels, and their functional as well as prognostic roles in acute myeloid leukemia. (28th November 2018) - Bertoli, Sarah; Paubelle, Etienne; Bérard, Emilie; Saland, Estelle; Thomas, Xavier; Tavitian, Suzanne; Larcher, Marie‐Virginie; Vergez, François; Delabesse, Eric; Sarry, Audrey; Huguet, Françoise; Larrue, Clément; et al.
Abstract: Objectives: We previously reported the prognostic value of serum ferritin in younger patients with intermediate‐risk acute myeloid leukemia (AML). The aims of this study were to confirm this finding in a larger cohort regardless of age and prognostic subgroups, to explore the expression and functional role of ferritin in AML cells as well as the regulation of serum ferritin levels in AML patients. Patients/Materials/Methods: Serum ferritin levels at diagnosis were collected in a cohort of 525 patients treated by intensive chemotherapy. In silico, in vitro, and in vivo analyses were conducted to assess the pattern of expression and functional role of FTH1 and FTL in AML. Results: We confirmed the independent prognostic value of serum ferritin. In transcriptomic databases, FTH1 and FTL were overexpressed in AML and leukemic stem cells compared to normal hematopoietic stem cells. The gene signature designed from AML patients overexpressing FTH1 revealed a significant enrichment in genes of the immune and inflammatory response including Nf‐KB pathway, oxidative stress, or iron pathways. This gene signature was enriched in cytarabine‐resistant AML cells in a patient‐derived xenograft model. FTH1 protein was also overexpressed in patient's samples and correlated with the in vitro cytotoxic activity of cytarabine. Lastly, we demonstrated that chemotherapy induced an inflammatory response including a significant increase in serum ferritin levels between day 1 and 8 of induction chemotherapy that was blocked by dexamethasone. Conclusion: Ferritin is deregulated in most AML patients likely through inflammation, associated with chemoresistance, and could represent a new therapeutic target.